Physical fitness, emotional intelligence, and learning motivation predict elementary students' physical education outcomes - Ida Rahmayani; Tjung Hauw Sin; Gusril Gusril; Nugroho Susanto; Andri Gemaini (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study examined the effects of physical fitness, emotional intelligence, and learning motivation on elementary students’ Physical Education learning outcomes. A quantitative associative design was employed involving 62 fifth-grade students at SD Negeri 82 Bengkulu City selected using Slovin’s formula. Data were collected through questionnaires and student report cards, then analyzed using regression and path analysis. Physical fitness, emotional intelligence, and learning motivation had significant direct effects on learning outcomes, with learning motivation emerging as the strongest predictor. Physical fitness and emotional intelligence also showed indirect effects through learning motivation, indicating the mediating role of motivation in improving achievement. Students’ Physical Education learning outcomes are shaped by physical, emotional, and motivational factors.